Creativity training for multifaceted inferences of reason behind others' behaviors. (March 2021) - Sannomiya, Machiko; Mashimo, Tomoko; Yamaguchi, Yosuke
Abstract: In the present study, an experiment was conducted to examine the effect of creativity training on the inference of reason behind others' behaviors using a repeated idea post-exposure (IPE) paradigm. The essential characteristic of this paradigm is that the participants are exposed to multiple inference examples as 'ideas of others' after they thought out ideas by themselves. The participants were 101 female students of a junior college. The target problems were young children's unusual behaviors, and the participants were asked to infer the reasons of those behaviors from multifaceted viewpoints as much as possible. We compared fluency and flexibility of idea generation in three conditions: training with IPE paradigm (IPE), training with no IPE paradigm (NIPE), and no training (control). The main results from the pre / post design experiment were as follows: 1) IPE was superior to control, 2) IPE was generally superior to NIPE in low performers, and 3) The effect of IPE appeared in the latter part of the training. These results were discussed through metacognitive facilitation of post-exposing others' ideas, especially for low performers.